2020
DOI: 10.1177/1557988320975542
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Commuting Time on Job Stress in Obese Men With Different Exercise Frequency in China

Abstract: Previous studies have mainly focused on the independent impact of commuting time, exercise, and stress on people. There are few studies regarding the impact of the combined effect of multiple factors on special populations such as obese people. As obesity has become increasingly widespread in China, we studied the impact of commuting time on work stress on Chinese obese men (who exercise regularly vs. who exercise irregularly). We performed a secondary retrospective analysis of the cross-sectional data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In the case of workers, a component of daily travel which has been shown to have relevant effects on health is travelling to work, or commuting ( Jacob et al, 2021 ). Longer commuting times have been associated with increased prevalence of obesity in workers ( Sha et al, 2019 ), as well as with increased levels of stress ( Zhu et al, 2020 ). Commuting mode choice has also shown to have relevant impacts on workers’ health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of workers, a component of daily travel which has been shown to have relevant effects on health is travelling to work, or commuting ( Jacob et al, 2021 ). Longer commuting times have been associated with increased prevalence of obesity in workers ( Sha et al, 2019 ), as well as with increased levels of stress ( Zhu et al, 2020 ). Commuting mode choice has also shown to have relevant impacts on workers’ health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sergio et al estimated the subjective values of travel time saving using perceptions results of work, leisure, and travel from a joint mode choice activity model [24]. It has been found that long commuting times have a positive and significant impact on increases in work stress and type of traveling mode also induces significant influence on stress [25,26]. Some of the factors influencing the VOT are summarized in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%